Single atom changes in newly synthesized HIV protease inhibitors reveal structural basis for extreme affinity, high genetic barrier, and adaptation to the HIV protease plasticity - Bulut, Haydar; Hattori, Shin-ichiro; Aoki-Ogata, Hiromi; Hayashi, Hironori; Das, Debananda; Aoki, Manabu; Davis, David A.; Rao, Kalapala Venkateswara; Nyalapatla, Prasanth R.; Ghosh, Arun K.; Mitsuya, Hiroaki (Scientific reports, 2020)
HIV-1 protease inhibitors (PIs), such as darunavir (DRV), are the key component of antiretroviral therapy. However, HIV-1 often acquires resistance to PIs. Here, seven novel PIs were synthesized, by introducing single atom changes such as an exchange of a sulfur to an oxygen, scission of a single bond in P2′-cyclopropylaminobenzothiazole (or -oxazole), and/or P1-benzene ring with fluorine scan of mono- or bis-fluorine atoms around DRV’s scaffold. X-ray structural analyses of the PIs complexed with wild-type Protease (PR WT ) and highly-multi-PI-resistance-associated PR DRV R P51 revealed that the PIs better adapt to structural plasticity in PR with resistance-associated amino acid substitutions by formation of optimal sulfur bond and adaptation of cyclopropyl ring in the S2′-subsite. Furthermore, these PIs displayed increased cell permeability and extreme anti-HIV-1 potency compared to DRV. Our work provides the basis for developing novel PIs with high potency against PI-resistant HIV-1 variants with a high genetic barrier.